Pengaruh Literasi Digital Terhadap Minat Membaca Al-Quran Digital Pada Mahasiswa Forum Komunikasi Dakwah Kampus (FKDK) UNSIKA - Awaliah , S. Koidatul; Abdurrohim; Mustofa, Taufik (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2024)
Abstract To be able to use, operate, and read the digital Quran, digital literacy skills are required. This study aims to: 1) find out how digital literacy is among students of the Campus Da'wah Communication Forum (FKDK) of Singaperbangsa University, Karawang, 2) find out how the interest in reading the digital Al-Quran is among students of the Campus Da'wah Communication Forum (FKDK) of Singaperbangsa University, Karawang, 3) find out whether there is an influence of digital literacy on the interest in reading the digital Al-Quran among students of the Campus Da'wah Communication Forum (FKDK) of Singaperbangsa University, Karawang. This study uses a quantitative approach with a correlational method. Data collection techniques used questionnaires, documentation, and observation. In this study, the population was 40 students, and the sample tested was 40 students with a probability sampling technique. The data analysis technique used descriptive analysis and inferential statistical analysis. Based on the results of the processed data, it was found that the digital literacy of FKDK UNSIKA students was in the moderate category with a percentage of 55.00% and the interest in reading the digital Al-Quran of FKDK UNSIKA students was in the moderate category with a percentage of 75.00% and there was a positive influence of digital literacy on the interest in reading the digital Al-Quran of FKDK UNSIKA students. This can be seen that the Sig value is 0.000 <0.05 with a percentage value of 61.4% while 38.6% is influenced by other variables. Abstrak Penelitian ini bertujuan untuk: 1) mengetahui bagaimana literasi digital pada mahasiswa Forum Komunikasi Dakwah Kampus (FKDK) Universitas Singaperbangsa Karawang, 2) mengetahui bagaimana minat membaca Al-Quran digital pada mahasiswa Forum Komunikasi Dakwah Kampus (FKDK) Universitas Singaperbangsa Karawang, 3) mengetahui adakah pengaruh literasi digital terhadap minat membaca Al-Quran digital pada mahasiswa Forum Komunikasi Dakwah Kampus (FKDK) Universitas Singaperbangsa Karawang. Penelitian ini menggunakan pendekatan kuanntitatif dengan metode korelasional. Teknik pengumpulan data yang dilakukan menggunakan angket, dokumentasi, dan observasi. Pada penelitian ini jumlah populasi sebanyak 40 mahasiswa, dan sampel yang diuji sebanyak 40 mahasiswa dengan teknik pengambilan sampel probability sampling. Teknik analisis data menggunakan analisis deskriptif dan analisis statistik inferensial. Berdasarkan hasil dari data yang sudah diolah, maka didapatkan bahwa literasi digital mahasiswa FKDK UNSIKA berada pada kategorisasi sedang dengan presentase sebesar 55,00% dan minat membaca Al-Quran digital mahasiswa FKDK UNSIKA berada pada kategorisasi sedang dengan presentase sebesar 75,00% serta adanya pengaruh yang positif literasi digital terhadap minat membaca Al-Quran digital pada mahasiswa FKDK UNSIKA. Hal tersebut dapat dilihat bahwa nilai Sig 0,000 < 0,05 dengan nilai presentase sebesar 61,4% sedangkan 38,6% dipengaruhi oleh variabel lain.